(untitled) (Revista Contexto & Educação, 2021)
This study deals with theoretical and practical reflections on interdisciplinary educational experiences developed in the early years of a public school in the countryside. Our objective was to understand how the pedagogical practices in the multi-grade classes in History, Geography and Natural Sciences classes have materialized in an interdisciplinary way considering the reality of the riverside communities. The methodology used was action research, as the active participation of the research object, the experience and intervention in the school context was sought. The investigated reality was a multiseries class of elementary school from the 2nd to the 5th year. The main focus was on the interdisciplinarity of the themes addressed, as well as a broad discussion on peasant communities in Brazil and the Amazon, as well as the identity and work of the subjects. The activities took place during 2018 at EMEF Fé em Deus, Rio Ana Igarapé, municipality of Igarapé-Miri, in the state of Pará. The results revealed that working with interdisciplinarity and dialogicity with heterogeneous classes in multiservice schools based on the principles of Freire’s generative themes allows teachers and students a promising dynamic for the teaching-learning process and for deepening the knowledge of social and school reality.